Generation Z and Information Visualization: Work from Home Managerial Task Context - Puspitasari, Nadya; Sekar J , Dyah (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
The remote working method, especially the work from home (WFH) method, will create its own challenges for employees, especially at the managerial level. Information visualization is used to present information in supporting the work from home process which in theory is expected to improve the quality of tasks and managerial decisions. Different generations may respond to remote work situations differently, so it is necessary to re-examine the effect of visualization in the context of work from home (WFH). in different generations. This study will examine whether there are differences in efficiency, effectiveness, and satisfaction of managerial decisions that work with the work from home (WFH) method when faced with information visualization and carried out by different generations. This test uses efficiency, effectiveness, and satisfaction as dependent variables, as well as information visualization and generation as independent variables. The participants used are practitioners and students who have or are currently carrying out assignments using the work from home (WFH) method. The type of data used in this study is primary data. The data in this study were collected using an experimental instrument with a given case. Based on the process of the instrument being distributed, 33 participants were obtained which could be further processed. Hypothesis testing in this study used Two-way Anova with software. The results showed that there were differences in the level of efficiency, effectiveness, and satisfaction of managerial decisions between participants who completed assignments with high information visualization and low information visualization. This study also shows that there is no difference in the level of efficiency, effectiveness, and managerial satisfaction between participants who complete assignments with generation Z and non-Z generations.